Climbing fiber-Purkinje cell synaptic pathology across essential tremor subtypes. (June 2018) - Lee, Danielle; Gan, Shi-Rui; Faust, Phyllis L.; Louis, Elan D.; Kuo, Sheng-Han
Abstract: Background: Essential tremor (ET) is heterogeneous in nature and cases may be subdivided based on clinical features. ET patients may thus be subdivided by age of onset, family history of tremor, and presence of head tremor. We recently described climbing fiber-Purkinje cell (CF-PC) synaptic abnormalities in ET; however, these CF pathological features have not been studied across different ET subtypes. Objectives: To explore whether these CF-PC synaptic abnormalities differ across ET subtypes. Methods: We studied two climbing fiber (CF-PC) synaptic pathologies (CF synaptic density and percentage of CFs in the parallel fiber [PF] territory) in the cerebella of 60 ET cases with a range of clinical presentations and 30 age-matched controls. Results: Compared to controls, ET cases had lower CF synaptic density and a higher percentage of CFs in the PF territory. ET cases with tremor onset <50 years and tremor onset ≥ 50 years did not differ significantly with respect to CF synaptic density and percentage of CFs in the PF territory. Similar results were found when comparing familial vs. sporadic ET cases, and ET cases with head tremor vs. those without head tremor. Among all ET cases, lower CF synaptic density was associated with lower PC counts and higher torpedo counts. In addition, higher percentage of CFs in the PF territory was associated with lower PC counts and higher torpedo counts. Conclusions: These findings support the notion that changes in the distribution of CF-PC synapses are broadly part of the neurodegenerative process in the ET cerebellum. Highlights: Climbing fiber (CF) synaptic pathology could be observed in essential tremor (ET) cerebellum. CF synaptic density is similarly decreased across different ET subtypes. CFs extending to the parallel fiber (PF) territory are increased in different ET subtyes. CF pathology correlates with Purkinje cell degenerative changes. CF pathology could be related to the core clinical feature of ET (kinetic tremor).